Analysis of Single and Multiple Sentences in Education Rubric in Kompas Newspaper - Anjelia Ratu Oasis; Nisrina Najla Rifa (LPPM State University of Jakarta (Program Studi Pendidikan Bahasa dan Sastra Indonesia dan LPPM Universitas Negeri Jakarta), 2022)
The purpose of this study is to describe single sentences and compound sentences in the education rubric of the Kompas newspaper. In this study a descriptive qualitative method was used which originated from the educational rubric of the Kompas newspaper October 27 ̶ 29 2022. The technology used to provide data is a tool that guides data analysis. The analysis technique of this research uses the process of collecting data using the listening method with note-taking techniques. In this study, apart from the analysis technique according to Moleong, there are four models, namely (1) data collection, (2) data reduction, (3) data presentation, and (4) conclusions. From the results of this study, researchers found several single sentences and compound sentences in the education rubric of the Kompas newspaper.